Metopic ridge—A physiological condition source of unjustified concern. - Garofalo, L.; Milano, A. (European Journal of Pediatric Dermatology, 2023)
The metopic suture, which connects the two outlines of the frontal bones, is the only one to close early, while the others close in adulthood. During the fusion process, a longitudinal thickening known as the metopic ridge sometimes forms. It has long been debated whether this crest constitutes a normal, physiological finding or instead represents a minimal form of trigonocephaly. A case is presented in a three-month-old child and the benignity of this clinical condition is underlined.